Carbon-coated aluminum foil with high binding power as well as preparation method and application of carbon-coated aluminum foil
By adding nanocellulose and nanocellulose composite materials to the coated aluminum foil and decomposing these materials after high-temperature baking, the problem of insufficient adhesion and toughness of the existing coated aluminum foil is solved, and higher adhesion and toughness are achieved, ensuring smooth operation.
Patent Information
- Application Number
- CN202510347310.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-24
AI Technical Summary
The current coated aluminum foil current collector has low adhesion and toughness, which affects subsequent slitting, rewinding and coating of positive electrode active materials.
The surface roughness and toughness of the coating layer are increased by adding nanocellulose and nanocellulose composites to the coating slurry and decomposing these materials after baking at high temperatures.
The adhesive force between the coated aluminum foil and the positive electrode active material is improved, the toughness of the coated layer is enhanced, and the subsequent operation is smooth.
Smart Images

Figure CN119890324A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a carbon-coated aluminum foil with high bonding strength, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely accepted in many fields such as consumer electronics, transportation, power tools and energy storage. Aluminum foil current collector refers to the process of combining aluminum foil with other materials (such as paper, plastic film, coating, etc.) to form a composite material. This technology can give aluminum foil new properties and functions to meet the needs of different industries. In order to improve the performance of lithium batteries, the lithium battery industry adopts the strategy of carbon-coated current collector to increase the rate of lithium batteries and improve the performance of lithium batteries.
[0003] However, the low adhesion of the carbon-coated aluminum foil current collector and the low toughness of the carbon-coated aluminum foil affect the subsequent slitting, rewinding, coating of positive electrode active materials and other operations. Therefore, it is necessary to develop and manufacture a carbon-coated aluminum foil with high adhesion to ensure a series of operations after carbonization, such as subsequent slitting, rewinding and coating of positive electrode slurry. Summary of the invention
[0004] In order to improve the bonding strength of carbon-coated aluminum foil, the present invention provides a carbon-coated aluminum foil with high bonding strength and a preparation method and application thereof. The present invention adopts the following technical scheme: A carbon-coated aluminum foil with high bonding strength, the carbon-coated aluminum foil with high bonding strength comprises a carbon-coated layer, the carbon-coated layer comprises a carbon conductive agent, nanocellulose and a nanocellulose composite material, the nanocellulose composite material is formed by compounding raw materials comprising nanocellulose and a thermally conductive and electrically conductive nanomaterial; The weight of the nanocellulose is 5-15% of the weight of the carbon conductive agent; The weight ratio of the nanocellulose to the nanocellulose composite material is 1:0.2-0.67; The thermal and electrical conductive nanomaterial is at least one of carbon nanotubes, transition metal disulfide, boron nitride nanomaterial and graphene material.
[0005] Preferably, the nanocellulose composite material is composed of nanocellulose and carbon nanotubes; Preferably, the weight ratio of nanocellulose to carbon nanotubes in the nanocellulose composite material is 1:(1.5-5); Preferably, the weight ratio of nanocellulose to carbon nanotubes in the nanocellulose composite material is 1:3; Preferably, the carbon nanotubes are single-walled carbon nanotubes.
[0006] Optionally, the carbon conductive agent comprises carbon powder; Preferably, the carbon conductive agent comprises carbon powder and graphite powder, and the weight ratio of the carbon powder to the graphite powder is 7-9:1-3.
[0007] A method for preparing a carbon-coated aluminum foil with high bonding strength comprises the following steps: Step 1) Compounding nanocellulose with thermally and electrically conductive nanomaterials to prepare a nanocellulose composite material; Step 2) mixing the raw materials including the nanocellulose composite material, nanocellulose, a carbon conductive agent and a binder to obtain a carbon-coated slurry; Step 3) coating the carbon-coated slurry on the aluminum foil to form a carbon-coated layer, thereby obtaining the carbon-coated aluminum foil.
[0008] Optionally, the nanocellulose is prepared by acid treatment using plant cellulose as raw material.
[0009] Optionally, the step 1) of compounding the nanocellulose and the thermally and electrically conductive nanomaterial to prepare the nanocellulose composite material comprises the following steps: The nanocellulose and the thermally and electrically conductive nanomaterials are mixed and then ground; and the ground mixture is then subjected to ultrasonic treatment in a solvent to obtain a nanocellulose composite material; Preferably, the thermally and electrically conductive nanomaterial is a carbon nanotube; Preferably, the diameter of the carbon nanotube is 1-5 nm, and the length of the carbon nanotube is 40-120 nm; Preferably, the nanocellulose and carbon nanotubes are mixed and ball-milled for 40-80 min at 800-1200 r / min, with a ball-milling zirconium bead size of 0.05-0.5 mm; the ground mixture is then ultrasonically treated in a solvent for 90-150 min at an ultrasonic frequency of 2000-4500 Hz to obtain a nanocellulose composite material.
[0010] Optionally, the raw material in step 2) further comprises a binder; Preferably, the method of uniformly mixing the raw materials comprising the nanocellulose composite material, nanocellulose, carbon conductive agent and binder in step 2) comprises the following steps: a) mixing a binder and a portion of a carbon conductive agent uniformly to obtain a mixture I; then adding nanocellulose to the mixture I and mixing uniformly to obtain a mixture II; b) adding the remaining carbon conductive agent to mixture II to obtain mixture III, and then adding the nanocellulose composite material to mixture III to obtain mixture IV; c) adjusting the pH of the mixture IV to 5-7 to obtain a carbon-coated slurry; Preferably, the binder is at least one of acrylate, polyacrylic acid, modified polyacrylic acid, and waterborne polyurethane; Preferably, in the step a), the binder is diluted with water and then evenly mixed with a portion of the carbon conductive agent to obtain a mixture I.
[0011] Optionally, the step 2) further includes: d) adding a wetting agent to the carbon coating slurry and mixing them uniformly, wherein the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohol wetting agent; Preferably, the amount of the wetting agent added is 5-10% of the mass of the carbon-coated slurry; Preferably, the step 2) further comprises: homogenizing the carbon-coated slurry.
[0012] The present invention also proposes the use of the carbon-coated aluminum foil with high bonding force in preparing a positive electrode of a battery.
[0013] A method for preparing a positive electrode of a battery comprises the following steps: The positive electrode material is coated on a carbon-coated layer of a carbon-coated aluminum foil having high bonding strength, and then pressed and heated to decompose and volatilize the nanocellulose composite material in the carbon-coated layer.
[0014] Preferably, the heating temperature of the heating treatment is 120-150°C and the time is 6-8 minutes; Preferably, the heating treatment is performed in an oven.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts the strategy of adding conventional nanocellulose and nanocellulose composite materials to the carbon-coated slurry, decomposes the nanocellulose composite materials by high-temperature baking, and leaves the position of cellulose on the surface of the carbon-coated aluminum foil after the decomposition of the nanocellulose composite materials, so that the roughness of the surface of the carbon-coated aluminum foil is increased. When the positive electrode active material is coated on the surface of the carbon-coated aluminum foil, the positive electrode active material will be embedded with the carbon-coated layer after rolling, and the combination will be more tightly, that is, the adhesion between the positive electrode active material and the carbon-coated layer is increased. In addition, the present invention also has a part of conventional nanocellulose in the carbon-coated layer, and the pyrolysis of these nanocelluloses is relatively high. After passing through the oven, only the nanocellulose composite materials are decomposed, and the retained conventional nanocellulose is left in the carbon-coated layer, which can reduce the deformation of the carbon-coated aluminum foil and increase the toughness of the carbon-coated layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a microscopic photograph of the surface of the carbon-coated aluminum foil of Example 1 after heat treatment.
[0018] Figure 2 This is a microscopic photograph of the surface of the carbon-coated aluminum foil of Comparative Example 3 after heat treatment.
[0019] Figure 3 This is a graph showing the thermogravimetric analysis results of the carbon-coated aluminum foil of Example 1. DETAILED DESCRIPTION
[0020] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0021] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0022] The raw materials used in the present invention are all commercially available products, and unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by conventional technicians in the field of the present invention. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention.
[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0024] The present invention provides a carbon-coated aluminum foil with high bonding strength, wherein the carbon-coated aluminum foil with high bonding strength comprises a carbon-coated layer, wherein the carbon-coated layer contains a carbon conductive agent, nanocellulose and a nanocellulose composite material, wherein the nanocellulose composite material contains nanocellulose and a thermally conductive and electrically conductive nanomaterial.
[0025] The weight of the nanocellulose is 10% of the weight of the carbon conductive agent; The weight ratio of the nanocellulose to the nanocellulose composite material is 1:0.2-0.67; The carbon conductive agent comprises carbon powder; further preferably, the carbon conductive agent comprises carbon powder and graphite powder, and the weight ratio of the carbon powder to the graphite powder is 7-9:1-3.
[0026] The present invention adopts the strategy of adding conventional nanocellulose and nanocellulose composite materials to the carbon-coated slurry, decomposes the nanocellulose composite materials by high-temperature baking, leaves the position of cellulose on the surface of the carbon-coated aluminum foil after decomposition, and increases the roughness of the surface of the carbon-coated aluminum foil. When the positive electrode active material is coated on the surface of the carbon-coated aluminum foil, the positive electrode active material will be embedded with the carbon-coated layer after rolling, and the combination will be more tightly, that is, the bonding force between the positive electrode active material and the carbon-coated layer is increased. In addition, there is a part of conventional nanocellulose in the carbon-coated layer, and the thermal decomposition of these nanocelluloses is relatively high. After passing through the oven, only the nanocellulose composite materials are decomposed, and the retained conventional nanocellulose is left in the carbon-coated layer, which can reduce the deformation of the carbon-coated aluminum foil and increase the toughness of the carbon-coated layer.
[0027] Nanocellulose is a new type of biomaterial obtained by nano-processing plant cellulose. It has excellent mechanical properties, thermal stability and biocompatibility, and is widely used in biomedicine, food, paper, textiles, building materials and other fields.
[0028] The nanocellulose composite material of the present invention uses a strategy of composite synthesis of thermally conductive and electrically conductive nanomaterials to decompose nanocellulose at a relatively low temperature. Since thermally conductive and electrically conductive nanomaterials themselves have some special properties, taking carbon nanotube (CNT) materials as an example: 1. High thermal conductivity. CNT has high thermal conductivity, which can quickly transfer heat and accelerate the decomposition of nanocellulose combined with it. 2. High surface area. CNT has a high surface area and can provide a large amount of contact area, promote the interaction between nanocellulose and CNT, and reduce the temperature required for the decomposition of nanocellulose. 3. Electronic conductivity: CNT has electronic conductivity, which can affect the electronic structure of nanocellulose and reduce the temperature required for its decomposition. Therefore, a nanocellulose composite material with a low pyrolysis temperature can be obtained by compounding thermally conductive and electrically conductive nanomaterials such as carbon nanotubes with nanocellulose.
[0029] The method for preparing the carbon-coated aluminum foil with high bonding strength comprises the following steps: Step 1) Compounding nanocellulose and thermally conductive and electrically conductive nanomaterials to obtain a nanocellulose composite material; the nanocellulose is prepared by acid treatment using plant cellulose as a raw material. The method of compounding nanocellulose and thermally conductive and electrically conductive nanomaterials includes the following steps: The nanocellulose and the heat-conducting and electrically-conducting nanomaterials are mixed and ground; the ground mixture is then ultrasonically treated in a solvent to obtain a nanocellulose composite material. The binder is at least one of acrylate, polyacrylic acid, modified polyacrylic acid, water-based polyurethane and the like.
[0030] Step 2) uniformly mixing raw materials including nanocellulose composite material, nanocellulose, carbon conductive agent and binder to obtain carbon-coated slurry; specifically comprising: a) mixing a binder and a portion of a carbon conductive agent uniformly to obtain a mixture I; then adding nanocellulose to the mixture I and mixing uniformly to obtain a mixture II; b) adding the remaining carbon conductive agent to mixture II to obtain mixture III, and then adding the nanocellulose composite material to mixture III to obtain mixture IV; c) adjusting the pH of the mixture IV to 5-7; d) then adding a wetting agent to the carbon-coated slurry and mixing them evenly, wherein the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohol wetting agent; and then using a homogenizer to perform homogenization twice to obtain the carbon-coated slurry.
[0031] Step 3) coating the carbon-coated slurry on the aluminum foil to form a carbon-coated layer, thereby obtaining the carbon-coated aluminum foil.
[0032] Further preferably, in the step 1), the binder is diluted with water and then evenly mixed with a portion of the carbon conductive agent to obtain a mixture I.
[0033] The present invention also proposes the use of the carbon-coated aluminum foil with high bonding force in preparing a positive electrode of a battery.
[0034] The present invention improves the bonding force between the carbon-coated aluminum foil and the positive electrode material by increasing the surface roughness of the carbon-coated layer. Increasing the surface roughness of the coating can effectively increase the positive electrode material coated on the carbon-coated layer. After rolling, the two materials have a greater interlocking force, that is, a greater electrode peeling force can be obtained. Increasing the surface roughness of the carbon-coated layer is achieved by decomposing the nanocellulose composite material present in the carbon-coated layer. The nanocellulose is mixed in the carbon slurry and coated on the surface of the aluminum foil. The nanocellulose composite material exists in the carbon-coated layer. The carbon-coated aluminum foil is passed through an oven, and the oven temperature is set at the decomposition and volatilization temperature of the nanocellulose composite material. The oven temperature can be set at 120-150°C, the oven length needs to be greater than 10m, and the heating time is 6-8min. After baking, the nanocellulose in the coating is decomposed and volatilized. The carbon-coated layer will have lines left by the nanocellulose composite material. These lines exist not only on the surface of the coating, but also inside the coating. This can greatly increase the roughness of the coating. After the positive active material and the coating are rolled, the interlocking force between the two will be greatly increased.
[0035] The present invention improves the toughness of carbon-coated aluminum foil by adding conventional nanocellulose. The principle that nanocellulose increases the toughness of carbon-coated aluminum foil is based on: 1. The high strength and high stiffness of nanocellulose. Nanocellulose has high strength and high stiffness, can provide strong mechanical support, and improve the toughness of the material. 2. The high surface area of nanocellulose: Nanocellulose has a high surface area, can provide a large amount of contact area, promote interaction between materials, and improve the toughness of materials. The pyrolysis temperature of conventional nanocellulose is 200-250°C. Therefore, after passing through a 120°C oven, conventional nanocellulose will not be affected and will still exist in the carbon-coated aluminum foil, playing a role in increasing the toughness of the carbon-coated aluminum foil.
[0036] Raw materials in the following embodiments: PAA was purchased from Sinopharm Group, model AR (Shanghai trial), ≥99.0% 500mL, Sinopharm code 80001418. Carbon powder was purchased from Shanghai Buding Chemical, model CABOT Cabot high wear-resistant carbon black N330. Graphite powder was purchased from McLean Group, model: G810361 graphite powder, 99.95% metals basis. Graphene was purchased from Sinopharm Group, model 97% (Wokai) 500mg, Sinopharm code XW011034343980012.
[0037] Example 1 A method for preparing a carbon-coated aluminum foil with high bonding strength comprises the following steps: Step 1) Preparation of nanocellulose and nanocellulose composites: In this embodiment, nanocellulose is prepared by chemically corroding plant cellulose with strong acid; acid treatment is a commonly used chemical method for obtaining nanocellulose. The principle of the acid treatment method is to use acid to hydrolyze the glycosidic bonds of plant cellulose and destroy the crystalline structure of cellulose, so as to obtain nanoscale cellulose. First, grind the plant cellulose for 1 hour, the grinding speed is 1000r / min, the pick bead size is 0.1mm, and the number is 20. The plant cellulose is crushed into small particles to increase its surface area. Then mix the plant cellulose powder with sulfuric acid, the concentration of sulfuric acid is 0.5mM / L, and the weight ratio of sulfuric acid to cellulose is 2:1 for reaction. The reaction temperature is room temperature (20°C) and the time is 9 hours. After the reaction is completed, neutralize the acidity and wash with deionized water to remove residual acid and other impurities. After drying at 50°C for 12 hours, nanocellulose is obtained.
[0038] Preparation of nanocellulose composite materials: The nanocellulose composite materials of the present invention use a strategy of composite synthesis of heat-conducting and electrically conductive nanomaterials to decompose nanocellulose at a lower temperature. Carbon nanotubes are selected from Merck Chemicals, single-walled carbon nanotubes, 750522, 98% (Semiconducting). The preparation of nanocellulose composite materials uses a simple material scheme ball milling method and ultrasonic synthesis method: take the prepared nanocellulose and single-walled carbon nanotubes and mix them in a weight ratio of 1:3, 1000r / min, ball mill for 60min, and choose 20 beads of 0.1mm size. Place the ball-milled mixture in a beaker and ultrasonicate for 120min at an ultrasonic frequency of 3500 Hz. Dry the treated sample in a drying oven at 50°C for 12 hours to obtain a nanocellulose composite material for standby use.
[0039] Step 2) S1: Deionized water and aqueous PAA are mixed in a weight ratio of 3:1 to reduce the solid content of the binder; a diluted binder is obtained, the volume of the diluted binder is 100 L, and the mass is 90 kg.
[0040] S2 Add 1.5 kg carbon powder and 1.5 kg graphite powder to the diluted binder and disperse at a high speed of 2000-2600 rpm / min in a 200L Double Star stirring tank for 30 minutes.
[0041] S3: Add 0.15 kg of nanocellulose and disperse in a 200 L double star stirring tank at 1000-1500 rpm / min for 30 min.
[0042] S4: Add 1.5kg carbon powder and 1.5kg graphite powder, and disperse at high speed of 2000-2600rpm / min in a 200L Double Star stirring tank for 60min.
[0043] S5: Add 15kg of deionized water to reduce the slurry concentration, and disperse at a high speed of 2000-2600rpm / min in a 200L Double Star stirring tank for 30min.
[0044] S6 added NaOH solution to adjust the pH to 6, weakly acidic.
[0045] S7 After the exotherm is over, add 0.1 kg of the nanocellulose composite material and disperse it in a 200 L double star stirring tank at 1000-1500 rpm / min for 60 min.
[0046] S8 Add 9 kg of isopropanol as a wetting agent, stir at a low speed of 10-15 rpm / min in a 200 L Double Star stirring tank for 30-45 min, and then discharge the material.
[0047] S9: Homogenize the slurry twice in a homogenizer at a pressure of 300 bar to obtain a carbon-coated slurry.
[0048] Step 3) The carbon coating slurry is coated on the aluminum foil to form a carbon coating layer, and the thickness of the carbon coating layer is 2 μm, thus obtaining the carbon coated aluminum foil.
[0049] The nanocellulose composite material in the carbon-coated aluminum foil coating will be decomposed and volatilized after baking. Figure 1 As shown in the figure, the carbon coating layer will have lines left by the nanocellulose composite material. Figure 1 The black area in the frame is the traces and lines left after the cellulose decomposes and curls up. These lines exist not only on the surface of the coating, but also inside the coating, which can greatly increase the roughness of the coating. After the positive electrode active material and the coating are rolled, the interlocking force between the two will be greatly increased.
[0050] The above nanocellulose composite material was subjected to thermogravimetric analysis test, and the test results are as follows Figure 3 As shown. Thermogravimetric analysis shows that the composite of carbon nanotubes and nanocellulose can be decomposed at a relatively low temperature of about 100°C. The composite material of carbon nanotubes and nanocellulose of the present invention can be decomposed in large quantities at a relatively low temperature. The principle mainly includes: a strong interface interaction (such as hydrogen bonding, van der Waals force or π-π stacking) is formed between carbon nanotubes and nanocellulose. These interactions may cause local stress concentration of nanocellulose segments, causing them to thermally decompose at a relatively low temperature. The addition of carbon nanotubes will destroy the ordered structure of nanocellulose, resulting in a decrease in its thermal stability. Carbon nanotubes have high thermal conductivity, and CNTs have high thermal conductivity, which can quickly transfer heat and accelerate the decomposition of nanocellulose combined with them. Carbon nanotubes have a high surface area, and CNTs have a high surface area, which can provide a large amount of contact area, promote the interaction between nanocellulose and CNTs, and reduce the temperature required for the decomposition of nanocellulose.
[0051] Example 2 Compared with Example 1, in step 2) of this example, the amount of conventional nanocellulose added is increased so that the addition ratio of conventional nanocellulose: nanocellulose composite material is 3:1, and the other steps are the same as in Example 1.
[0052] Example 3 Compared with Example 1, in step 2) of this embodiment, the amount of conventional nanocellulose added is increased so that the addition ratio of conventional nanocellulose: nanocellulose composite material is 4:1, and the other steps are the same as in Example 1.
[0053] Example 4 Compared with Example 1, in step 2) of this example, the amount of conventional nanocellulose added is increased so that the addition ratio of conventional nanocellulose: nanocellulose composite material is 5:1, and the other steps are the same as in Example 1.
[0054] Example 5 Compared with Example 1, in step 1) of this embodiment, the carbon nanotubes are replaced with graphene of the same weight. The remaining steps are the same as those of Example 1.
[0055] Example 6 Compared with Example 1, in step 1) of this embodiment, the carbon nanotubes are replaced with an equal weight of molybdenum disulfide. The remaining steps are the same as those of Example 1.
[0056] Comparative Example 1 Compared with Example 1, conventional nanocellulose is not added in step 2). The remaining steps are the same as those in Example 1.
[0057] Comparative Example 2 Compared with Example 1, conventional nanocellulose and nanocellulose composite material are not added in step 2). The remaining steps are the same as those in Example 1.
[0058] Comparative Example 3 Compared with Example 1, no nanocellulose composite material is added in step 2). The remaining steps are the same as in Example 1. The microscopic picture of the carbon-coated aluminum foil coating of this comparative example after baking is as follows: Figure 2 As shown, compared with Example 1, the surface of this comparative example lacks the traces and lines left after the cellulose decomposition and curling formed in Example 1, and the surface roughness is relatively low, which will cause insufficient bonding force after rolling.
[0059] Test example: The positive electrode material is coated on the carbon coating layer of each embodiment and comparative example, and then passed through an oven. The oven temperature is set at the solvent temperature of the nanocellulose composite material, the oven temperature is set at 120°C, the oven length needs to be greater than 10m, and the heating time is 7min. After baking, the nanocellulose in the coating is decomposed and volatilized. Rolling is performed to prepare the positive electrode, and the rolling compaction density is 2.35g / cm 2 .
[0060] After preparation, the pole piece peeling force and tensile strength test of each embodiment and comparative example sample were tested. The pole piece peeling force test method was as follows: the pole piece after rolling was cut into 10 x 2 cm size. The test was performed using an electronic peeling tester. The cut pole piece sample was pasted onto the tested stainless steel plate with a 2 cm wide 3M tape, and one side of the pole piece was opened for a 180° pole piece peeling test. After the test was completed, the experimental parameters were recorded.
[0061] Tensile strength test method: Use a Tesla universal tensile machine to test, cut the carbon-coated foil into 15 x 1.5 cm strips, clamp the strips on the universal tensile machine, test the tensile speed at 100 mm / min, and record the experimental data after the test. The test results are shown in Table 1: Table 1 Test results
[0062] According to the performance comparison of the above embodiments and comparative examples, the added nano-cellulose composite material will be decomposed and volatilized after baking, which can greatly increase the roughness of the coating. After the positive electrode active material and the coating are rolled, the interlocking force between the two will be greatly increased, while the comparative example without adding the nano-cellulose composite material has a lower electrode peeling force.
[0063] Adding conventional nanocellulose can significantly improve the toughness of aluminum foil, and the tensile strength of the control sample without adding nanocellulose is significantly lower.
[0064] The above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention, rather than to limit them. Although the embodiments of the present invention are described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon-coated aluminum foil with high bonding strength, characterized in that: The carbon-coated aluminum foil with high bonding strength comprises a carbon-coated layer, wherein the carbon-coated layer contains a carbon conductive agent, nanocellulose and a nanocellulose composite material, wherein the nanocellulose composite material is formed by compounding raw materials comprising nanocellulose and a thermally conductive and electrically conductive nanomaterial; The weight of the nanocellulose is 5-15% of the weight of the carbon conductive agent; The weight ratio of the nanocellulose to the nanocellulose composite material is 1:0.2-0.67; The thermal and electrical conductive nanomaterial is at least one of carbon nanotubes, transition metal disulfide, boron nitride nanomaterial and graphene material.
2. The carbon-coated aluminum foil with high bonding strength according to claim 1, characterized in that: The weight ratio of nanocellulose to carbon nanotubes in the nanocellulose composite material is 1:1.5-5.
3. The carbon-coated aluminum foil with high bonding strength according to claim 1, characterized in that: The carbon conductive agent includes carbon powder; or the carbon conductive agent includes carbon powder and graphite powder, and the weight ratio of the carbon powder to the graphite powder is 7-9:1-3.
4. The method for preparing a carbon-coated aluminum foil having high bonding strength according to any one of claims 1 to 3, characterized in that: The steps include: Step 1) Compounding nanocellulose with thermally and electrically conductive nanomaterials to prepare a nanocellulose composite material; Step 2) mixing the raw materials including the nanocellulose composite material, nanocellulose and carbon conductive agent uniformly to obtain a carbon-coated slurry; Step 3) coating the carbon-coated slurry on the aluminum foil to form a carbon-coated layer, thereby obtaining the carbon-coated aluminum foil.
5. The preparation method according to claim 4, characterized in that: The nanocellulose is prepared by using plant cellulose as raw material through an acid treatment method.
6. The preparation method according to claim 4, characterized in that The method of preparing the nanocellulose composite material by compounding the nanocellulose and the thermally and electrically conductive nanomaterial in step 1 comprises the following steps: The nanocellulose and the thermally and electrically conductive nanomaterial are mixed and then ground; and the ground mixture is then subjected to ultrasonic treatment in a solvent to obtain a nanocellulose composite material; and / or The thermally and electrically conductive nanomaterial is a carbon nanotube; the diameter of the carbon nanotube is 1-5 nm, and the length of the carbon nanotube is 40-120 nm; and / or The nanocellulose and carbon nanotubes are mixed and ball-milled for 40 to 80 minutes at 800 to 1200 r / min, with the ball-milling zirconium beads having a size of 0.05 to 0.5 mm; the ground mixture is then ultrasonically treated in a solvent for 90 to 150 minutes at an ultrasonic frequency of 2000 to 4500 Hz to obtain a nanocellulose composite material.
7. The preparation method according to claim 4, characterized in that: The raw materials in step 2) further include a binder; and / or The method of uniformly mixing the raw materials including the nanocellulose composite material, nanocellulose, carbon conductive agent and binder in step 2) comprises the following steps: Step a) mixing a binder and a portion of a carbon conductive agent uniformly to obtain a mixture I; then adding nanocellulose to the mixture I and mixing uniformly to obtain a mixture II; Step b) adding the remaining carbon conductive agent to mixture II to obtain mixture III, and then adding the nanocellulose composite material to mixture III to obtain mixture IV; Step c) adjusting the pH of the mixture IV to 5-7 to obtain a carbon-coated slurry; and / or The binder is at least one of acrylate, polyacrylic acid, modified polyacrylic acid and waterborne polyurethane; and / or In the step a), the binder is diluted with water and then evenly mixed with a portion of the carbon conductive agent to obtain a mixture I.
8. The preparation method according to claim 7, characterized in that The step 2) also includes: d) adding a wetting agent to the carbon coating slurry and mixing the mixture evenly, wherein the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohol wetting agent; and / or The amount of the wetting agent added is 5-10% of the mass of the carbon-coated slurry; and / or The step 2) also includes: homogenizing the carbon-coated slurry.
9. Use of the carbon-coated aluminum foil with high adhesion as claimed in any one of claims 1 to 3 in preparing a positive electrode of a battery.
10. A method for preparing a positive electrode of a battery, characterized in that: The steps include: The positive electrode material is coated on the carbon coating layer of the carbon-coated aluminum foil with high bonding force as claimed in any one of claims 1 to 3, and then pressed and heated to decompose and volatilize the nanocellulose composite material in the carbon coating layer.
Citation Information
Patent Citations
Lithium ion battery copper / aluminum foil coating water-based conductive paste and preparation method thereof
CN111009664A
High-performance lithium battery current collector, conductive slurry and preparation method thereof
CN116259929A
Preparation method of laminated heterostructure microelectrode based on screen printing
CN118352168A
Lithium ion battery bionic structure deformation electrode prepared based on 3D printing technology
CN118888682A
Cellulose nanofibres-based electroconductive composite having carbon nanotubes inserted into crystalline or non-crystalline regions of cellulose nanofibers to form an electric pathway network
KR102083427B1